Optimizing the latency of the 4G network by using Routing Algorithm / Rossidah Wan Abdul Aziz ... [et al.] - Wan Abdul Aziz, Rossidah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
4G is a technology that will revolutionize how people communicate. This technology has been around for a long time and is now widely employed by individuals and businesses. In this research, data from users in the research area is collected to evaluate the services provided to analyze which ones are better and the best mobile operator in providing 4G services. One of the most serious concerns is network latency, which is primarily affected by the operational area and the speed of the servers themselves, and is a disadvantage of all communication networks, including2G and 3G. Extreme latency is becoming increasingly common as networks grow. This research objective is to determine minimum network latency using a Routing Algorithm in 4G network and to classify which 4G network operators arethe best by using Routing Algorithm. The Routing Algorithm hasbeen used todetermine the route or path that data packets will take from source to destination. They help to ensure that internet traffic is routed efficiently (Xia, Zhang, Yu, & Pan, 2016).